2012
DOI: 10.1177/2150131911435673
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Implementation of a Self-management Program in Resource Poor and Rural Community Clinics

Abstract: Although only about a third of patients remained engaged through the 2 follow-up calls, most of those who did reported they had achieved their action plan. This pilot study provides insight into initiating brief diabetes self-management strategies in resource-poor community clinics. Although telephone follow-up was challenging, using the self-management guide and action plan framework, particularly during the initial clinic visit, helped focus patients on behavior change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
(27 reference statements)
0
4
1
Order By: Relevance
“…Previous studies of resource-poor community clinics or Appalachian dwelling people have demonstrated favorable effects related to patients' engagement in their own chronic care. However, this study did not support previous findings that educational strategies to enhance patients' self-care efforts (Davis et al, 2012), or self-management activities (Jessee et al, 2012) are effective in improving importanthealthcare outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies of resource-poor community clinics or Appalachian dwelling people have demonstrated favorable effects related to patients' engagement in their own chronic care. However, this study did not support previous findings that educational strategies to enhance patients' self-care efforts (Davis et al, 2012), or self-management activities (Jessee et al, 2012) are effective in improving importanthealthcare outcomes.…”
Section: Discussioncontrasting
confidence: 99%
“…During study week 7, participants created a short-term action plan focused on behavior change related to self-management of chronic disease and/or health maintenance using video and written materials outlining the well-established SMART goal framework. 25,62 Participants then reported their level of action plan initiation in the action plan initiation (API) survey, 72 from 1 (not at all) to 7 (completely) at weeks 8 and 9, a 2-week time window consistent with previously published studies. 26,72,73 Evidence of plan initiation was defined as API score ≄ 5.…”
Section: Primary Outcomementioning
confidence: 99%
“…[17][18][19][20] Selfmanagement, a core focus within both the PCMH health care reform movement and the Chronic Care Model, 18,[20][21][22][23] is commonly encouraged through a process of engaged goal setting using the SMART framework 24 and accessible to a diversity of patient populations. 25,26 Mindfulness meditation may enhance self-regulation [27][28][29] (e.g., attention, emotion regulation processes 30,31 ) by increasing cognitive resources 28 (e.g., reappraisal, exposure) and modifying self-related processing 32 (e.g., reduced rumination, enhanced body awareness). Mindfulness-based programs (MBPs) 33 , derived from mindfulness-based stress reduction (MBSR), 34,35 are evidence-based treatments that seem to harness self-regulatory mechanisms and could help people with self-regulation challenges catalyze behavior change related to managing chronic disease.…”
Section: Introductionmentioning
confidence: 99%
“…The full-text versions of the remaining articles were reviewed for eligibility resulting in the exclusion of 224 for the reasons noted. Ultimately, 62 studies were included from the search, reporting on 60 unique patient samples 23 25–86…”
Section: Resultsmentioning
confidence: 99%